The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1210/jc.2005-2361
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin Is a Human Placental Product That Regulates Glucose Uptake

Abstract: Myostatin is synthesized, released, and acts within the human placenta. It contributes to placental glucose homeostasis and may be a therapeutic target in diseases ranging from placental insufficiency to diabetes in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 14 publications
1
56
0
Order By: Relevance
“…The effect of myostatin on placental glucose transport is mixed, with decreased glucose transport in a choriocarcinoma cell line (27) and increased transport in human placental explants (28). Myostatin also promotes extravillous trophoblast migration in vitro, which may alter placental development in vivo (29).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of myostatin on placental glucose transport is mixed, with decreased glucose transport in a choriocarcinoma cell line (27) and increased transport in human placental explants (28). Myostatin also promotes extravillous trophoblast migration in vitro, which may alter placental development in vivo (29).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment of term placental explants with 1 g/mL of myostatin increased glucose uptake (16). Supporting myostatin's potential role in modulating glucose uptake, Chen et al (17) recently reported that myostatin treatment led to a dosedependent increase in glucose uptake in C2C12 myotubles and L6 myocytes.…”
mentioning
confidence: 93%
“…In human placentae, myostatin expression is negatively correlated with gestational age, with myostatin protein significantly higher in early and preterm placentae as compared with term placentae (16). Furthermore, treatment of term placental explants with 1 g/mL of myostatin increased glucose uptake (16).…”
mentioning
confidence: 98%
“…Wider functions of myostatin are supported by the discovery of myostatin expression in a number of different tissues, including brain (35), mammary (23), cardiac (39), adipose (28), endometrium (38), and human placenta (29). One particularly interesting finding is the changing myostatin expression throughout gestation in the human placenta.…”
mentioning
confidence: 99%
“…One particularly interesting finding is the changing myostatin expression throughout gestation in the human placenta. Mitchell et al (29) have shown that there is a negative correlation in human placenta between myostatin expression and gestational age, with a higher myostatin expression evident in preterm human placental tissues compared with term placental tissues. Additional in vitro studies also found that myostatin regulates glucose uptake in human placenta (3,29).…”
mentioning
confidence: 99%